El "Tercero transparencial" en la escritura de Macedonio Fernández - Seimandi, Favio G. D. (Centro de Investigaciones de la Facultad de Filosofía y Humanidades, 2011)
This work, entitled The "Transparent Third" in the writing of Macedonio Fernández, is directed to generate a critical dialogue about certain philosophic interpretations of the abovementioned author. We think that the hermeneutic gaze search profoundly, in the other side of the words, the trace of the concept and let escape the most adjoining and superficial level in which the writing is deployed in its specificity. This gaze destroys the inherent of the writing because it puts the reader in the scene of the writing-reading, in its immediate reality.Our critic proposes quite a wide approach to the texts of Macedonio Fernández and analyses several topics of his work critical studies –his ideas about philosophy, politics, laws, his opposition to realism and representation, the privilege of affection-, to show the existence of an structural space, where writing is conceived as a series of intersubjective positions directed to generate a possible experience. In this case, this is the experience of opening the conscience to the infinite finitude, to the affection immortality which is not transcendental.